2019
DOI: 10.1111/jifm.12106
|View full text |Cite
|
Sign up to set email alerts
|

Rating and capital structure: How do the signs affect the speed of adjustment?

Abstract: Standard and Poor's ratings can be modified by the addition of a plus (+) or minus (−) sign to show the relative standing within each major rating category. In this paper, we analyze the influence of these signs on the speed of leverage adjustment for listed European companies in the 2004–2014 period. Our results indicate that (a) when a qualification is accompanied by a minus sign, it adjusts more slowly than qualifications either with a plus sign or without a sign; (b) when a rating has a plus sign, the adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
(118 reference statements)
0
6
0
Order By: Relevance
“…There is also an increase in debt costs related to the rise in interest rates and inflation, in addition to an increase in the premium charged by international creditors to compensate for the risk inherent in the countries. In this context, several studies have presented empirical evidence on the effects of sovereign ratings on both the performance and debt of firms (Cai et al, 2019;Chen et al, 2013;Jesuka & Peixoto, 2022;Joo & Parhizgari, 2021;Medina & Di Pietro, 2019). Chen et al (2013) investigated the effects of sovereign rating changes in 48 countries on corporate investment over the period 1983-2009 and found that there were significant increases in private investment growth after sovereign rating upgrades, as well as significant and temporary declines in investment after sovereign rating downgrades.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also an increase in debt costs related to the rise in interest rates and inflation, in addition to an increase in the premium charged by international creditors to compensate for the risk inherent in the countries. In this context, several studies have presented empirical evidence on the effects of sovereign ratings on both the performance and debt of firms (Cai et al, 2019;Chen et al, 2013;Jesuka & Peixoto, 2022;Joo & Parhizgari, 2021;Medina & Di Pietro, 2019). Chen et al (2013) investigated the effects of sovereign rating changes in 48 countries on corporate investment over the period 1983-2009 and found that there were significant increases in private investment growth after sovereign rating upgrades, as well as significant and temporary declines in investment after sovereign rating downgrades.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Chen et al (2013) investigated the effects of sovereign rating changes in 48 countries on corporate investment over the period 1983-2009 and found that there were significant increases in private investment growth after sovereign rating upgrades, as well as significant and temporary declines in investment after sovereign rating downgrades. Medina and Di Pietro (2019) investigated the effects of rating changes on the speed of leverage adjustment of listed European firms over the period 2004-2014 and reported that a rating downgrade decision adjusts capital structure more slowly than an upgrade.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, other studies on the effects of credit ratings on non-financial firms' capital structure (Kisgen, 2009;Samaniego-Medina and di Pietro, 2019;Wojewodzki et al, 2018) highlight the importance of borderline (between investment and non-investment grade) credit ratings on capital structure. This is due to regulatory restrictions imposed on institutional investors in the U.S. and other countries (Kisgen, 2019), thereby negatively affecting non-investment grade firms' costs of external finance and pool of investors.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The first contribution is aimed at verifying how the attribution of the external rating can influence the choices on the financial structure of the companies. The article by Samaniego‐Medina and Di Pietro () (“Rating and capital structure. How do the signs affect the speed of adjustment?”) explores the influence that the attribution of a rating of a particular class has on the degree of leverage.…”
mentioning
confidence: 99%